2012
DOI: 10.5144/1658-3876.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Post-dengue fever severe aplastic anemia: a rare association

Abstract: Dengue fever has rarely been reported as an etiology for aplastic anemia. An 8-year-old girl was admitted with fever, myalgia and petechiae. Dengue virus IgM antibodies were positive. She recovered completely, but her thrombocytopenia persisted. Six weeks later she became pancytopenic. A bone marrow aspirate and biopsy showed severe aplastic anemia. She was treated with antithymocytic immunoglobulin, methylprednisolone and cyclosporine. She became transfusion independent 6 months later. Dengue-virus induced ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…A fall in Hb and packed cell volume instead of the usual hemoconcentration during the critical phase can be associated with gut bleeding. However, true aplastic anemia has been described with DF, and some of these cases have been attributed to hemophagocytic syndrome [14] and others to bone marrow suppression [15, 16]. Our patient did not undergo a bone marrow biopsy; hence, it is impossible to differentiate bone marrow pathology from a peripheral pathology.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A fall in Hb and packed cell volume instead of the usual hemoconcentration during the critical phase can be associated with gut bleeding. However, true aplastic anemia has been described with DF, and some of these cases have been attributed to hemophagocytic syndrome [14] and others to bone marrow suppression [15, 16]. Our patient did not undergo a bone marrow biopsy; hence, it is impossible to differentiate bone marrow pathology from a peripheral pathology.…”
Section: Discussionmentioning
confidence: 87%
“…However, a very low reticulocyte index of 0.2% indicated that the former is more likely. Aplastic anemia reported with dengue had been treated with intravenously administered immunoglobulins, steroids, and cyclosporine [15, 16]. Our patient was already on immunosuppressives; hence, the aplastic crisis could have become self-limited with the medications she was already receiving.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there have been reports of successful control of massive bleeding due to thrombocytopenia in two DENV patients with pulmonary and gastrointestinal bleeding [2]. Moreover, DENV infection can even lead to bone marrow failures [3] with a suppression and complete destruction of bone marrow cells. In addition, DHF can be associated with hemophocytic lymphohistiocytosis, characterized by benign generalized histiocytic proliferation with marked hemophagocytosis.…”
Section: Denv Associated Bleedingmentioning
confidence: 98%
“…Although the pathophysiology of DENV-induced BM failure is not well understood, accumulating evidence indicates a combination of an excessive immune response and viral infection of progenitor cells ( 62 , 63 ). During the acute phase of infection, DENV infects and proliferates in HSC progenitors and CD61+ megakaryocyte progenitor cells ( 60 , 64 ), thereby inducing transient BMF ( 63 ).…”
Section: Dengue Virus (Denv)-induced Bm Failurementioning
confidence: 99%